Pengambilan Keputusan Petani untuk Tetap Berusahatani Cabe Jamu di Kecamatan Bluto, Sumenep - Anisah, Anisah; Hayati, Mardiyah (AGRARIS: Journal of Agribusiness and Rural Development Research, 2017)
This research aims to determine the factors that influence farmer decision to keep his long pepper farming in Bluto District. This research was conducted in 5 villages of the long pepper production center. A samples of 86 farmers was analized by an analysis of binary logistic. The result showed that factor influencing the farmer decision to keep his long pepper farming was the experience of farming. Increasing experience of farming will upgrade farmer knowledges in minimizing failure on long pepper farming.